Do Angry Birds Make for Angry Children? A Meta-Analysis of Video Game Influences on Children's and Adolescents' Aggression, Mental Health, Prosocial Behavior, and Academic Performance. (September 2015) - Ferguson, Christopher J.
The issue of whether video games—violent or nonviolent—"harm" children and adolescents continues to be hotly contested in the scientific community, among politicians, and in the general public. To date, researchers have focused on college student samples in most studies on video games, often with poorly standardized outcome measures. To answer questions about harm to minors, these studies are arguably not very illuminating. In the current analysis, I sought to address this gap by focusing on studies of video game influences on child and adolescent samples. The effects of overall video game use and exposure to violent video games specifically were considered, although this was not an analysis of pathological game use. Overall, results from 101 studies suggest that video game influences on increased aggression ( r = .06), reduced prosocial behavior ( r = .04), reduced academic performance ( r = −.01), depressive symptoms ( r = .04), and attention deficit symptoms ( r = .03) are minimal. Issues related to researchers' degrees of freedom and citation bias also continue to be common problems for the field. Publication bias remains a problem for studies of aggression. Recommendations are given on how research may be improved and how the psychological community should address video games from a public health perspective.